Tracing the Roots of Radicalism and Terrorism: Muhammad Ibn Alawi Al-Maliki’s Thought Related to Extremism Discourse - Mohammad Rindu Fajar Islamy (Religio: Jurnal Studi Agama-agama, 2021)
This study aims to explore the thoughts of Sayyid Muhammad bin Alawi Al-Maliki regarding extremist behavior where this action is allegedly the raw material for the ideology of radicalism which is certainly contradictory to the values ​​of Islamic teachings. The phenomenon of radical, anarchic, brutal acts, and even terrorism which has increased recently has caused unrest and anxiety not only for the government, but this issue has also raised concerns for religious leaders in various parts of the world. Senior international scholar Sayyid Muhammad bin Alawi Al-Maliki is one of the scholars who pays attention to the discourse of radicalism. Al-Maliki who is seen as one of the descendants of the Prophet Muhammad SAW has a moderate view in throwing his views on the issue. Al-Ghuluwwu Wa Atsaruhu fi Al-Irhab wa Ifsad Al-Mujtama is his phenomenal work criticizing the ideology of extremism as fuel for acts of terrorism. The concept of "takfir" according to Sayyid Muhammad bin Alawi is one of the root causes of the increase in acts of terror that occur everywhere.